Problem-based Learning Strategies and Gender as Determinant of Grade 9 Students' Academic Achievement in Algebra - Olaoye, Olabisi; Adu, Emmanuel O. (International journal of educational sciences, 2015)
This study examined the effects of problem based learning strategies and gender on students' academic achievement. A 3X2 pre-test and post-test control group quasi-experimental group design was adopted in the study. The instruments constructed and used for the study were: Problem Based Learning Strategies which are in two parts (PBLSa), (PBLSb) and Conventional Teaching Guide (C.T.G). Two hypotheses were generated and tested in the study at 0.05 alpha levels. One of the major findings of this study was that (PBLSa) and (PBLSb) are more effective than conventional method in students' academic achievement in algebra (x= 3.05; SE =.720), (= 4.23; SE=.714), (= 3.36; SE =.726) in that order. The study also revealed there is no significant main effect of gender on students' academic achievement, female(= 15.63) and male (= 15.41). However, the study recommended that problembased learning strategies should be embraced by both the teachers and learners in order to enhance students' academic achievement in algebra.